71‐4: Laser Phosphor Light Source using Compound Reflectors for Projection Display. Issue 1 (28th June 2022) - Li, Kenneth; Chang, Y.P; Chen, Andy; Tsai, Stark; Wang, Lion
Abstract : A compound reflector made up of two ellipsoidal reflectors is used to transfer the emission from the laser excited focal spot on the phosphor plate to another location in space without change in etendue and with minimum loss. This allows the excitation optics to be separated from the collection optics so that they could be designed with more flexibility and higher efficiency. These also allow the generation of sequential RGB output with the addition of white (W), i.e. RGBW, which is not possible using traditional optics.